KOMUNIKASI KEMASJIDAN DALAM PEMAKMURAN MESJID PERSPEKTIF KOMUNIKASI ORGANISASI - Robeet Thadi (Program Studi Manajemen Dakwah Fakultas Dakwah dan Komunikasi Islam Institut Agama Islam (IAI) Al-Azhaar Lubuklinggau, 2021)
Abstract:. This article aims to explain the form of mosque communication and the direction of organizational communication in the prosperity of mosques in the perspective of organizational communication. The method used in this research is literature study. The nature of the study conducted is descriptive analysis, the type of data used is secondary data. Data analysis through reduction, presentation and data simulation. In prospering mosques, mosque communication has an important contribution, through five forms of mosque communication: communication between administrators, communication with congregations, program communication, communication between congregations and communication between mosques. In the communication perspective, the direction of information flow in mosque communication is in line with the direction of organizational communication, namely downward communication, upward communication, horizontal communication and interline communication. Maximizing each function of the flow of communication is believed to create a prosperous mosque. Abstrak: Artikel ini bertujuan menjelaskan bagaimana bentuk komunikasi kemesjidan dan arah komunikasi organisasi dalam pemakmuran masjid perspektif komunikasi organisasi. Metode yang digunakan dalam penelitian ini adalah studi kepustakaan, adapun sifat dari studi yang dilakukan adalah deskriptif analisis, jenis data yang digunakan data sekunder. Analisis data melalui reduksi, penyajian dan penyimulan data. Dalam memakmurkan masjid, komunikasi kemasjidan memiliki andil yang penting, melalui lima bentuk komunikasi kemasjidan: komunikasi antarpengurus, komunikasi dengan jamaah, komunikasi program, komunikasi antar jama’ah dan komunikasi antar masjid. Pada perspektif komunikasi arah aliran informasi komunikasi kemasjidan sejalan dengan arah komunikasi organisasi yakni downward communication, upward communication, horizontal communication dan interline communication. Memaksimalkan masing-masing fungsi aliran komunikasi diyakini akan tercipta masjid yang makmur.